Analysis of United States Cyberpower Domination through the Cloud Act on Data Security in Europe - Triwahyuni, D; Nugraha, Y W; Permana, I R H; Falentino, Z A (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to analyze the dominance of US cyberpower through the Cloud Act on data security in Europe. Currently, the business of storing and processing data via a network, commonly known as the cloud, is dominated by US technology giants. Meanwhile in Europe, business people and governments failed to reach an agreement to form a cloud service to match that dominance. One of the causes of European concern is the law in the US called the Cloud Act. This agreement provides for complying with their obligations to store, back up, or disclose electronic data in their possession regardless of where that information is located. That way, the United States can have special access to be able to access state data without the need for a warrant. The research method used is descriptive qualitative with data collection techniques through interviews, documentation, and literature study from books and e-journals. Determination of informants using purposive sampling method. the validity and reliability of the data were tested using data triangulation techniques. The results of the analysis in this study show the dominance of US cyberpower in the global cloud system business. The conclusion of this study is that it is very important to build readiness in facing the onslaught of American cyber power dominance starting from setting regulations that can be agreed upon by the international community by prioritizing technological modernization so that every country has the same opportunity to build and secure its own cloud system